2012
DOI: 10.1016/j.jhep.2012.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Nilotinib protects the murine liver from ischemia/reperfusion injury

Abstract: Background & Aim The mitogen-activated protein kinases (MAPKs) c-Jun N-terminal kinase (JNK) and p38 mediate liver ischemia/reperfusion (I/R) injury via cell death and inflammatory cytokine expression, respectively. Nilotinib is an orally available receptor tyrosine kinase inhibitor used for chronic myelogenous leukemia that also has in vitro activity against JNK and p38. In this study, we examine its therapeutic potential against hepatic I/R injury. Methods The effects of nilotinib on liver I/R injury were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 50 publications
2
43
1
Order By: Relevance
“…JNK is related to the occurrence and development of tumors [25], ischemia-reperfusion (I/R) injury [26], immune inflammatory response [27], and other diseases. JNK is mainly localized in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…JNK is related to the occurrence and development of tumors [25], ischemia-reperfusion (I/R) injury [26], immune inflammatory response [27], and other diseases. JNK is mainly localized in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…assessment of interleukin-6 (Il-6), tumor necrosis factor-α (TNF-α) and macrophage inflammatory protein-2 (MIP-2) levels IL-6, TNF-α and MIP-2 levels were estimated using the previously reported methods. 45,46 Blood was collected after reperfusion for 12 h and centrifuged at 3,600× g for 15 min to gain the sera. IL-6, TNF-α and MIP-2 levels were measured using commercially available kits.…”
Section: Liver Function Assessmentmentioning
confidence: 99%
“…Previous studies have shown that TNF-α, IL-6 and MIP-2 inflammatory cytokines and oxidative stress injury significantly increased HI/RI. 46,53 Some studies have affirmed that BMP-2 reduced TNF-α, IL-6 and oxidative stress injury in I/R injury. 15,16 In this study, BMP-2, BMP-2/PEG-b-PLL and BMP-2/ GA-PEG-b-PLL decreased TNF-α, IL-6 and MIP-2 inflammatory cytokines and oxidative stress injury in HI/RI ( Figure 6B-D).…”
mentioning
confidence: 99%
“…One of them is Nilotinib (receptor tyrosine kinase inhibitor), and its protective role against liver cell damage. One recent study has shown that Nilotinib lowers both liver Jun Nterminal kinases (JNK) activation and neural progenitor cells (NPC) p 38 mitogen-activated protein kinase (MAPK) activation in mice, and may be useful in ameliorating liver IRI in humans (79). All of the aforementioned methods are summarized in Table 2.…”
Section: Nilotinibmentioning
confidence: 99%